A self-catalyzed reaction of 1, 2-dibenzoyl-o-carborane with hydrosilanes – formation of new hydrofuranes. Issue 70 (14th August 2019) - Jaiswal, Kuldeep; Volodarsky, Solomon; Kampel, Vladimir; Dobrovetsky, Roman
Abstract : FLP-type Si–H bond activation by carbonyls in 1, 2-dibenzoyl- o -carborane leading to new hydrofuranes with an o -carboranyl backbone in a self-catalyzed reaction. Abstract : The activation of Si–H bonds is a very important transformation both in organic and inorganic chemistry. Herein we report that 1, 2-dibenzoyl- o -carborane (1 ) reacts with Si–H bonds, yielding new hydrofurane-type products. The mechanism of this Si–H bond activation was studied both experimentally and by DFT calculations, and supposedly proceeds in an FLP-type manner.